2013
DOI: 10.1590/s1516-14392013005000178
|View full text |Cite
|
Sign up to set email alerts
|

Steel corrosion assessment by electrochemical impedance on metakaolin blended mortars

Abstract: Since Corrosion of reinforcing steel in concrete is the cause of major economic losses, Portland cement has been traditionally replaced by cements blended with pozzalanic materials, most of which have been found to reduce the corrosion of steel. This paper shows the results of an experimental research aimed to investigate the corrosion of reinforcement in mortar using electrochemical impedance spectroscopy (EIS). For this, concrete laboratory samples containing a 0.0055 m steel bar and prepared with just ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The impedance values for blended concretes are greater than the impedance values for the remaining specimens. Triana et al [52] assert that MK-blended concretes increase the impedance values over the entire frequency range, which is consistent with the results in this study. Fig.…”
Section: Linear Polarisation Resistance and Eissupporting
confidence: 93%
“…The impedance values for blended concretes are greater than the impedance values for the remaining specimens. Triana et al [52] assert that MK-blended concretes increase the impedance values over the entire frequency range, which is consistent with the results in this study. Fig.…”
Section: Linear Polarisation Resistance and Eissupporting
confidence: 93%
“…The current state of knowledge on the influence of the SCMs studied here on the passivation behavior of embedded steel and corrosion-inducing chloride content Comparative investigation on the influence of metakaolin, metaillite and steel slag as SCMs in mortar on the corrosion behavior of embedded steel varies: While some studies on concrete [18][19][20][21], mortar [22,23], and cement paste [24] are already available for the use of metakaolin as well as a review on durability by Homayoonmehr et al [25], no such studies are known for the use of metaillite or steel slag.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Electrochemical techniques by measuring the open circuit potential and by recording the electrochemical impedance spectrum. Indeed, it has already been shown that Electrochemical Impedance Spectroscopy (EIS) is a powerful technique to study the corrosion of metal or alloy embedded in a cement-based material [9][10][11][12][13][14][15]. This method offers the advantage to avoid any perturbation on the metal/paste interface if the measurement is carried out at the open circuit potential.…”
Section: Introductionmentioning
confidence: 99%